Mutations of ATIC and ADSL affect purinosome assembly in cultured skin fibroblasts from patients with AICA-ribosiduria and ADSL deficiency - Baresova, Veronika; Skopova, Vaclava; Sikora, Jakub; Patterson, David; Sovova, Jana; Zikanova, Marie; Kmoch, Stanislav (Human molecular genetics, 2012)
The purinosome is a multienzyme complex composed by the enzymes active in de novo purine synthesis (DNPS) that cells transiently assemble in their cytosol upon depletion or increased demand of purines. The process of purinosome formation has thus far been demonstrated and studied only in human epithelial cervical cancer cells (HeLa) and human liver carcinoma cells (C3A) transiently expressing recombinant fluorescently labeled DNPS proteins. Using parallel immunolabeling of various DNPS enzymes and confocal fluorescent microscopy, we proved purinosome assembly in HeLa, human hepatocellular liver carcinoma cell line (HepG2), sarcoma osteogenic cells (Saos-2), human embryonic kidney cells (HEK293), human skin fibroblasts (SF) and primary human keratinocytes (KC) cultured in purine-depleted media. Using the identical approach, we proved in cultured skin fibroblasts from patients with AICA-ribosiduria and ADSL deficiency that various mutations of ATIC and ADSL destabilize to various degrees of purinosome assembly and found that the ability to form purinosomes correlates with clinical phenotypes of individual ADSL patients. Our results thus shown that the assembly of functional purinosomes is fully dependent on the presence of structurally unaffected ATIC and ADSL complexes and presumably also on the presence of all the other DNPS proteins. The results also corroborate the hypothesis that the phenotypic severity of ADSL deficiency is mainly determined by structural stability and residual catalytic capacity of the corresponding mutant ADSL protein complexes, as this is prerequisite for the formation and stability of the purinosome and at least partial channeling of succinylaminoimidazolecarboxamide riboside-ADSL enzyme substrates-through the DNPS pathway.
Keywords: mutace; HeLa Cells; keratinocyty; Autistic Disorder; Keratinocytes; autistická porucha; Cell Line, Tumor; Multienzyme Complexes; Fibroblasts; puriny; Purine-Pyrimidine Metabolism, Inborn Errors; Adenylosuccinate Lyase; lidé; HeLa buňky; kůže; Mutation; fibroblasty; Nucleotide Deaminases; kultivované buňky; poruchy metabolismu purinů a pyrimidinů; Hydroxymethyl and Formyl Transferases; Cells, Cultured; multienzymové komplexy; hydroxymethyltransferasy a formyltransferasy; Skin; adenylsukcinátlyasa; Purines; deaminasy nukleotidů; nádorové buněčné linie; Humans